A novel cell‐penetrating peptide derived from WT1 enhances p53 activity, induces cell senescence and displays antimelanoma activity in xeno‐ and syngeneic systems. Issue 1 (21st January 2014) - Massaoka, Mariana H.; Matsuo, Alisson L.; Figueiredo, Carlos R.; Girola, Natalia; Faria, Camyla F.; Azevedo, Ricardo A.; Travassos, Luiz R.
Abstract : The Wilms tumor protein 1 (WT1) transcription factor has been associated in malignant melanoma with cell survival and metastasis, thus emerging as a candidate for targeted therapy. A lysine–arginine rich peptide, WT1‐pTj, derived from the ZF domain of WT1 was evaluated as an antitumor agent against A2058 human melanoma cells and B16F10‐Nex2 syngeneic murine melanoma. Peptide WT1‐pTj quickly penetrated human melanoma cells and induced senescence, recognized by increased SA‐β‐galactosidase activity, enhanced transcriptional activity of p53, and induction of the cell cycle inhibitors p21 and p27. Moreover, the peptide bound to p53 and competed with WT1 protein for binding to p53. WT1‐pTj treatment led to sustained cell growth suppression, abrogation of clonogenicity and G2/M cell cycle arrest. Notably, in vivo studies showed that WT1‐pTj inhibited both the metastases and subcutaneous growth of murine melanoma in syngeneic mice, and prolonged the survival of nude mice challenged with human melanoma cells. The 27‐amino acid cell‐penetrating WT1‐derived peptide, depends on C 3 and H 16 for effective antimelanoma activity, inhibits proliferation of WT1‐expressing human tumor cell lines, and may have an effective role in the treatment of WT1‐expressing malignancies. Abstract : WT1‐pTj is a Lys‐Arg‐rich peptide derived from the ZF domain of Wilms tumor protein 1. WT1‐pTj peptide protects syngeneic mice against metastatic melanoma. WT1‐pTj delays melanoma development after tumor induction and early growth. Trojan WT1‐pTj delays melanoma cell cycle, binds to and activates p53. WT1‐pTj activates p21 and p27 and induces senescence features.